A wear-resistant zirconium oxide ceramic material and preparation method thereof
By using components such as zirconia nanosheets, titanium carbide powders and modified nano calcium fluoride, combined with ultrasonic stirring, ball milling and vacuum hot pressing sintering, wear-resistant zirconia ceramic materials with high hardness and toughness are prepared, which solves the problem of insufficient fracture toughness of existing ceramic materials and significantly improves their wear resistance and service life.
Patent Information
- Application Number
- CN202411957737.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
AI Technical Summary
The fracture toughness of existing wear-resistant zirconia ceramic materials needs to be improved, and it is difficult to maintain surface smoothness and shape stability under high load friction environments.
Zirconia nanosheets, titanium carbide powder and modified nano calcium fluoride are used as main components, and wear-resistant zirconia ceramic materials are prepared through ultrasonic stirring, ball milling and vacuum hot pressing sintering.
It significantly improves the overall hardness and toughness of ceramic materials, enhances its wear resistance and impact resistance during friction, and extends its service life.
Smart Images

Figure CN119751059A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ceramic materials, in particular to a wear-resistant zirconia ceramic material and a preparation method thereof. Background Art
[0002] Chinese patent publication number CN108558393B discloses a wear-resistant zirconia ceramic comprising the following components by weight: 70-85 parts zirconium oxide; 8-15 parts calcium mixture; 3-6 parts modified alumina; 8-15 parts binder; and 8-12 parts surfactant. The modified alumina enhances the recrystallization ability of the zirconia, allowing the tetragonal zirconia phase to remain at room temperature or lower, increasing the toughness of the zirconia ceramic. Furthermore, the modified alumina maintains a relatively stable specific surface area and does not decrease dramatically. This stability allows the zirconia ceramic to absorb significant energy and resist crack formation. The zirconia ceramic exhibits high resistance to repeated deformation and fatigue spalling, resulting in excellent wear resistance. The calcium mixture is added to the zirconia ceramic to increase the structural strength of the material, imparting high hardness and wear resistance. The fracture toughness of the zirconia ceramics prepared using the aforementioned prior art solutions needs to be improved. Therefore, the present invention provides a wear-resistant zirconia ceramic material and preparation method to address the aforementioned issues. Summary of the Invention
[0003] In view of the deficiencies in the prior art, the present invention provides a wear-resistant zirconia ceramic material and a preparation method thereof, which solve the problems mentioned in the above background technology.
[0004] To achieve the above objectives, the present invention is implemented through the following technical solution: a wear-resistant zirconia ceramic material, comprising the following components in parts by weight: 20-30 parts of zirconia nanosheets, 10-20 parts of titanium carbide powder, 8-15 parts of modified nano-calcium fluoride, and 40-70 parts of anhydrous ethanol.
[0005] A method for preparing a wear-resistant zirconia ceramic material, specifically comprising the following preparation steps:
[0006] Step 1: Add equal amounts of anhydrous ethanol to the weighed zirconium oxide nanosheets, titanium carbide powder, and modified nano-calcium fluoride, respectively, and stir ultrasonically for 15-30 minutes, then mix the components and continue ultrasonic stirring for 10-20 minutes;
[0007] Step 2: Pour the mixed material into a ball mill under nitrogen atmosphere, add grinding balls at a mass ratio of 10:1 between balls and ceramic material, and ball mill for 4-5 hours;
[0008] Step 3: Place the product in a vacuum drying oven at 100-110° C. and dry for 20-24 hours, then take it out, grind it, sieve it, place it in a graphite mold, cold-press it, and sinter it in a vacuum hot-pressing sintering furnace to obtain a wear-resistant zirconia ceramic material.
[0009] Preferably, in the step three, the product is ground and passed through a 180-200 mesh sieve.
[0010] Preferably, the preparation method of the zirconium oxide nanosheets is:
[0011] Under a nitrogen atmosphere, the zirconium oxide nanosheet precursor is placed in a tubular furnace, heated to 450-600° C., kept warm and calcined for 1.8-2 hours, and then cooled to room temperature in the furnace to obtain zirconium oxide nanosheets.
[0012] Preferably, during the heating process, the heating rate is 3-5°C / min.
[0013] Preferably, the preparation method of the zirconium oxide nanosheet precursor is:
[0014] (1) Pour 9-12 mmol of carbamide into 30-45 mL of a 0.8-2 mol / L aqueous zirconium nitrate solution and stir until completely dissolved;
[0015] (2) After heating to 140-160°C, keep warm for 6-8 hours, and then cool naturally to room temperature;
[0016] (3) After filtering the product, it is washed with deionized water and anhydrous ethanol in sequence, and finally placed in a freeze drying oven at 0-2°C for 20-24 hours to obtain a zirconium oxide nanosheet precursor.
[0017] Preferably, the preparation method of the modified nano calcium fluoride is:
[0018] 1) Add 25-35 mL of dispersant to 8-12 g of nano-calcium fluoride and ultrasonicate for 45-60 min;
[0019] 2) Heat the water bath to 45-60°C while stirring, then add 30-40 mL of distilled water, and then add ammonia dropwise to adjust the pH of the solution to 7.5-9.5;
[0020] 3) Slowly add 2.5-4 g of ethyl orthosilicate dropwise, raise the temperature to 70-80°C, and stir the reaction for 4-5 hours;
[0021] 4) Centrifuge for 20-30 minutes, then wash with anhydrous ethanol 3-5 times;
[0022] 5) Place in 45-60 mL of a 1:1 volume ratio of n-butanol and distilled water mixed solvent and ultrasonically stir for 20-30 minutes;
[0023] 6) performing azeotropic distillation treatment, and then drying in a drying oven at 50-65° C. for 10-12 hours to obtain modified nano-calcium fluoride.
[0024] Preferably, the preparation method of the dispersant is: pouring polyethylene glycol into anhydrous ethanol and ultrasonically treating for 30-60 minutes to obtain the dispersant; wherein the volume ratio of polyethylene glycol to anhydrous ethanol is 1.2:(1-1.5).
[0025] Preferably, the preparation method of the nano calcium fluoride is:
[0026] ① Under stirring conditions, pour 1.5-2.5g of dispersant into 5-8mL of 1mol / L calcium nitrate solution and sonicate for 20-30min to prepare solution A; pour 2-3.5mL of dispersant into 6-10mL of 2.5mol / L ammonium fluoride solution and sonicate for 20-30min to prepare solution B;
[0027] ②Slowly add solution A to solution B under stirring. After the addition is complete, react for 40-60 minutes and then allow to stand for 2-3 hours.
[0028] ③ Centrifuge at a speed of 3500-4000 r / min for 45-60 minutes, then wash with distilled water for 3-5 times, and finally dry in a drying oven at 55-65° C. for 6-8 hours to obtain nano calcium fluoride.
[0029] Beneficial effects
[0030] The present invention provides a wear-resistant zirconia ceramic material and a preparation method. Compared with the prior art, it has the following advantages:
[0031] (1) The wear-resistant zirconia ceramic material and preparation method thereof, since the zirconia nanosheets themselves have a relatively high hardness, the overall hardness of the prepared ceramic material is also effectively improved, making it more resistant to external friction and wear, and can maintain good surface smoothness and shape stability under high-load friction environments; at the same time, during the friction process, the zirconia nanosheets can form a lubricating film on the ceramic surface, reducing the friction coefficient, reducing wear, further improving the wear resistance of the ceramic material, and extending its service life; and the zirconia nanosheets can play a role of dispersion strengthening in the ceramic matrix, hindering the expansion of cracks, thereby improving the toughness of the ceramic material and reducing the risk of fracture due to impact or stress concentration during use.
[0032] (2) The wear-resistant zirconia ceramic material and preparation method thereof, by adding modified nano-calcium fluoride, make it more tightly bonded with the ceramic matrix, effectively improve the overall hardness of the ceramic, and make it less susceptible to wear during friction, thereby significantly improving the wear resistance of the wear-resistant ceramic material; and it can be filled into the microscopic pores of the ceramic material, thereby increasing the density of the material and thereby enhancing the hardness and wear resistance; and the modified nano-calcium fluoride can form a flexible connection between the ceramic particles, and when the material is impacted, it can absorb and disperse energy, reduce the generation and expansion of cracks, thereby improving the toughness and impact resistance of the wear-resistant ceramic material. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The XRD spectra of nano-calcium fluoride and modified nano-calcium fluoride provided by the present invention are shown. DETAILED DESCRIPTION
[0034] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0035] In the present technical solution, the preparation method of the dispersant is as follows: pouring polyethylene glycol into anhydrous ethanol and ultrasonically treating for 45 minutes to obtain the dispersant; wherein the volume ratio of polyethylene glycol to anhydrous ethanol is 1.2:1.
[0036] Example 1
[0037] A method for preparing a wear-resistant zirconia ceramic material, specifically comprising the following preparation steps:
[0038] Step 1: add equal amounts of anhydrous ethanol to 20 g of zirconium oxide nanosheets, 10 g of titanium carbide powder, and 8 g of modified nano-calcium fluoride, respectively, and stir ultrasonically for 15 min. Then, mix the components and continue ultrasonic stirring for 10 min.
[0039] The preparation method of zirconia nanosheets is as follows: 9 mmol of carbonamide is poured into 30 mL of a 0.8 mol / L zirconium nitrate aqueous solution and stirred until completely dissolved; after heating to 140°C, the temperature is kept for 6 hours, and then naturally cooled to room temperature; after filtering the product, it is washed with deionized water and anhydrous ethanol in sequence, and finally placed in a freeze drying oven at 0°C for 20 hours to obtain a zirconia nanosheet precursor; under a nitrogen atmosphere, the zirconia nanosheet precursor is placed in a tubular furnace, heated to 450°C at a heating rate of 3°C / min, calcined for 1.8 hours, and then cooled to room temperature with the furnace to obtain zirconia nanosheets;
[0040] The preparation method of modified nano calcium fluoride is:
[0041] (1) Under stirring conditions, 1.5 g of dispersant was poured into 5 mL of 1 mol / L calcium nitrate solution and ultrasonically treated for 20 min to obtain solution A; 2 mL of dispersant was poured into 6 mL of 2.5 mol / L ammonium fluoride solution and ultrasonically treated for 20 min to obtain solution B; under stirring conditions, solution A was slowly added dropwise to solution B. After the addition was completed, the solution was reacted for 40 min and then aged for 2 h; the solution was centrifuged at 3500 r / min for 45 min, then washed with distilled water 3 times, and finally dried in a drying oven at 55°C for 6 h to obtain nano-calcium fluoride;
[0042] (2) Add 25 mL of dispersant to 8 g of nano-calcium fluoride and ultrasonically treat for 45 min; under stirring, heat the water bath to 45 ° C, then add 30 mL of distilled water, and then add ammonia water to adjust the pH value of the solution to 7.5; slowly add 2.5 g of tetraethyl orthosilicate, heat to 70 ° C, and stir for 4 h; centrifuge for 20 min, and then wash with anhydrous ethanol 3 times; place in 45 mL of a mixed solvent of n-butanol and distilled water with a volume ratio of 1:1, and ultrasonically stir for 20 min; perform azeotropic distillation, and then dry in a drying oven at 50 ° C for 10 h to obtain modified nano-calcium fluoride;
[0043] Step 2: Pour the mixed material into a ball mill under nitrogen atmosphere, add grinding balls at a mass ratio of balls to ceramic material of 10:1, and ball mill for 4 hours;
[0044] Step 3: Place the product in a vacuum drying oven at 100°C and dry for 20 hours. Then, take it out, grind it, and pass it through a 180-mesh sieve. Place it in a graphite mold and cold-press it into shape. Sinter it in a vacuum hot-pressing sintering furnace to obtain a wear-resistant zirconia ceramic material.
[0045] Example 2
[0046] A method for preparing a wear-resistant zirconia ceramic material, specifically comprising the following preparation steps:
[0047] Step 1: Add equal amounts of anhydrous ethanol to 25 g of zirconium oxide nanosheets, 15 g of titanium carbide powder, and 10 g of modified nano-calcium fluoride, respectively, and stir ultrasonically for 15 minutes. Then, mix the components and continue ultrasonic stirring for 15 minutes.
[0048] The preparation method of zirconia nanosheets is as follows: 10 mmol of carbonamide is poured into 35 mL of a 1.5 mol / L zirconium nitrate aqueous solution and stirred until completely dissolved; after heating to 150°C, the temperature is kept for 7 hours, and then naturally cooled to room temperature; after filtering the product, it is washed with deionized water and anhydrous ethanol in sequence, and finally placed in a freeze drying oven at 1°C for 22 hours to obtain a zirconia nanosheet precursor; under a nitrogen atmosphere, the zirconia nanosheet precursor is placed in a tubular furnace, heated to 500°C at a heating rate of 4°C / min, kept warm for 1.9 hours, and then cooled to room temperature with the furnace to obtain zirconia nanosheets;
[0049] The preparation method of modified nano calcium fluoride is:
[0050] (1) Under stirring conditions, 2 g of dispersant was poured into 6 mL of a 1 mol / L calcium nitrate solution and ultrasonically treated for 25 min to obtain solution A; 3 mL of dispersant was poured into 8 mL of a 2.5 mol / L ammonium fluoride solution and ultrasonically treated for 250 min to obtain solution B; under stirring conditions, solution A was slowly added dropwise to solution B. After the addition was completed, the solution was reacted for 50 min and then aged for 2.5 h; the solution was centrifuged at 3800 r / min for 50 min, then washed with distilled water 4 times, and finally dried in a drying oven at 60°C for 7 h to obtain nano-calcium fluoride;
[0051] (2) Add 30 mL of dispersant to 10 g of nano-calcium fluoride and ultrasonically treat for 50 min; under stirring, heat the water bath to 50 ° C, then add 35 mL of distilled water, and then add ammonia water to adjust the pH value of the solution to 8.5; slowly add 3.54 g of ethyl orthosilicate, heat to 75 ° C, and stir for 4.5 h; centrifuge for 25 min, and then wash with anhydrous ethanol 4 times; place in 50 mL of a mixed solvent of n-butanol and distilled water with a volume ratio of 1:1, and ultrasonically stir for 25 min; perform azeotropic distillation, and then dry in a drying oven at 60 ° C for 11 h to obtain modified nano-calcium fluoride;
[0052] Step 2: Pour the mixed material into a ball mill under nitrogen atmosphere, add grinding balls at a mass ratio of balls to ceramic material of 10:1, and ball mill for 4.5 hours;
[0053] Step 3: Place in a vacuum drying oven at 105°C and dry for 22 hours, take out, grind, and pass through a 190-mesh sieve, place in a graphite mold and cold press, and sinter in a vacuum hot pressing sintering furnace to obtain a wear-resistant zirconia ceramic material.
[0054] Example 3
[0055] A method for preparing a wear-resistant zirconia ceramic material, specifically comprising the following preparation steps:
[0056] Step 1: add equal amounts of anhydrous ethanol to 30 g of zirconium oxide nanosheets, 20 g of titanium carbide powder, and 15 g of modified nano-calcium fluoride, stir ultrasonically for 15 min, mix the components, and continue ultrasonic stirring for 20 min;
[0057] The preparation method of zirconia nanosheets is as follows: 12 mmol of carbonamide is poured into 45 mL of a 2 mol / L zirconium nitrate aqueous solution and stirred until completely dissolved; after heating to 160°C, the temperature is kept for 8 hours, and then naturally cooled to room temperature; after filtering the product, it is washed with deionized water and anhydrous ethanol in sequence, and finally placed in a freeze drying oven at 2°C for 24 hours to obtain a zirconia nanosheet precursor; under a nitrogen atmosphere, the zirconia nanosheet precursor is placed in a tube furnace, heated to 600°C at a heating rate of 5°C / min, calcined for 2 hours, and then cooled to room temperature with the furnace to obtain zirconia nanosheets;
[0058] The preparation method of modified nano calcium fluoride is:
[0059] (1) Under stirring conditions, 2.5 g of dispersant was poured into 8 mL of 1 mol / L calcium nitrate solution and ultrasonically treated for 30 min to obtain solution A; 3.5 mL of dispersant was poured into 0 mL of 2.5 mol / L ammonium fluoride solution and ultrasonically treated for 230 min to obtain solution B; under stirring conditions, solution A was slowly added dropwise to solution B, after the addition was completed, the reaction was carried out for 60 min, and then the solution was aged for 3 h; the solution was centrifuged at a speed of 4000 r / min for 60 min, then washed with distilled water 5 times, and finally dried in a drying oven at 65°C for 8 h to obtain nano calcium fluoride;
[0060] (2) Add 35 mL of dispersant to 12 g of nano-calcium fluoride and ultrasonically treat for 60 min; under stirring, heat the water bath to 60 ° C, then add 40 mL of distilled water, and then add ammonia water to adjust the pH value of the solution to 9.5; slowly add 4 g of tetraethyl orthosilicate, heat to 80 ° C, and stir for 5 h; centrifuge for 30 min, and then wash with anhydrous ethanol 5 times; place in 60 mL of a mixed solvent of n-butanol and distilled water with a volume ratio of 1:1, and ultrasonically stir for 30 min; perform azeotropic distillation, and then dry in a drying oven at 65 ° C for 12 h to obtain modified nano-calcium fluoride;
[0061] Step 2: Pour the mixed material into a ball mill under nitrogen atmosphere, add grinding balls at a mass ratio of balls to ceramic material of 10:1, and ball mill for 5 hours;
[0062] Step 3: Place the product in a vacuum drying oven at 110°C and dry for 24 hours, then take it out, grind it, pass it through a 200-mesh sieve, place it in a graphite mold and cold-press it into shape, and sinter it in a vacuum hot-pressing sintering furnace to obtain a wear-resistant zirconia ceramic material.
[0063] Comparative Example 1
[0064] Compared with Example 1, the difference is that the zirconium oxide nanosheets in Example 1 are replaced by zirconium oxide; the rest remain unchanged.
[0065] Comparative Example 2
[0066] Compared with Example 1, the difference is that the modified nano-calcium fluoride in Example 1 is replaced by nano-calcium fluoride; the rest remains unchanged.
[0067] The elastic modulus, hardness, fracture toughness and wear resistance of the samples were tested; the results are shown in Table 1.
[0068] Table 1
[0069]
[0070]
[0071] like Figure 1 As shown in the XRD spectrum of nano-calcium fluoride, all identifiable peaks are consistent with the data of pure cubic calcium fluoride crystals. The diffraction peaks of calcium fluoride crystals are narrow and sharp, indicating that the prepared calcium fluoride has high crystallinity and complete structure. No diffraction peaks or impurity peaks of other phases are found. The XRD spectrum of modified nano-calcium fluoride is the same as that of pure cubic calcium fluoride crystals, but there is a wide and short peak package at 2θ=20-25°, which represents the generation of amorphous silicon dioxide. During the coating process, silicon dioxide exists in an amorphous form.
[0072] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.
[0073] It should be noted that, in this document, relational terms such as first and second, etc., are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "comprises," "comprising," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a list of elements includes not only those elements but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus.
[0074] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. A wear-resistant zirconia ceramic material, characterized in that: The invention comprises the following components in parts by weight: 20-30 parts of zirconium oxide nanosheets, 10-20 parts of titanium carbide powder, 8-15 parts of modified nano calcium fluoride and 40-70 parts of anhydrous ethanol.
2. A method for preparing the wear-resistant zirconia ceramic material according to claim 1, characterized in that: The specific preparation steps include: Step 1: adding equal amounts of anhydrous ethanol to the weighed zirconium oxide nanosheets, titanium carbide powder, and modified nano-calcium fluoride, respectively, stirring the mixture by ultrasonic for 15-30 minutes, and then mixing the components, and continuing ultrasonic stirring for 10-20 minutes; Step 2: Pour the mixed material into a ball mill under nitrogen atmosphere, add grinding balls at a mass ratio of 10:1 between balls and ceramic material, and ball mill for 4-5 hours; Step 3: Place in a vacuum drying oven at 100-110° C. and dry for 20-24 hours, take out, grind, sieve, place in a graphite mold for cold pressing, and sinter in a vacuum hot pressing sintering furnace to obtain a wear-resistant zirconia ceramic material.
3. The method for preparing a wear-resistant zirconia ceramic material according to claim 2, characterized in that: In the step 3, the powder is ground and then passed through a 180-200 mesh sieve.
4. The method for preparing a wear-resistant zirconia ceramic material according to claim 2, characterized in that: The preparation method of the zirconium oxide nanosheet is as follows: Under a nitrogen atmosphere, the zirconium oxide nanosheet precursor is placed in a tubular furnace, heated to 450-600° C., calcined for 1.8-2 hours, and then cooled to room temperature with the furnace to obtain the zirconium oxide nanosheet.
5. The method for preparing a wear-resistant zirconia ceramic material according to claim 4, characterized in that: During the heating process, the heating rate is 3-5°C / min.
6. The method for preparing a wear-resistant zirconia ceramic material according to claim 4, characterized in that: The preparation method of the zirconium oxide nanosheet precursor is: (1) Pour 9-12 mmol of carbamide into 30-45 mL of a 0.8-2 mol / L aqueous zirconium nitrate solution and stir until completely dissolved; (2) After heating to 140-160°C, keep warm for 6-8 hours, and then cool naturally to room temperature; (3) After filtering the product, it is washed with deionized water and anhydrous ethanol in sequence, and finally placed in a freeze drying oven at 0-2°C for 20-24 hours to obtain a zirconium oxide nanosheet precursor.
7. The method for preparing a wear-resistant zirconia ceramic material according to claim 2, characterized in that: The preparation method of the modified nano calcium fluoride is: 1) Add 25-35 mL of dispersant to 8-12 g of nano calcium fluoride and perform ultrasonic treatment for 45-60 min; 2) Heat the water bath to 45-60°C under stirring, then add 30-40 mL of distilled water, and then add ammonia water dropwise to adjust the pH value of the solution to 7.5-9.5; 3) Slowly add 2.5-4 g of ethyl orthosilicate, raise the temperature to 70-80°C, and stir to react for 4-5 hours; 4) Centrifuge for 20-30 minutes, then wash with anhydrous ethanol 3-5 times; 5) Place in 45-60 mL of a mixed solvent of n-butanol and distilled water in a volume ratio of 1:1, and stir ultrasonically for 20-30 min; 6) Perform azeotropic distillation treatment, and then place in a drying oven at 50-65° C. for 10-12 hours to obtain modified nano calcium fluoride.
8. The method for preparing a wear-resistant zirconia ceramic material according to claim 7, characterized in that: The preparation method of the dispersant is as follows: pouring polyethylene glycol into anhydrous ethanol and ultrasonically treating for 30-60 minutes to obtain the dispersant; wherein the volume ratio of polyethylene glycol to anhydrous ethanol is 1.2:(1-1.5).
9. The method for preparing a wear-resistant zirconia ceramic material according to claim 8, characterized in that: The preparation method of the nano calcium fluoride is: ① Under stirring conditions, pour 1.5-2.5 g of the dispersant into 5-8 mL of a 1 mol / L calcium nitrate solution, and ultrasonically treat for 20-30 min to obtain solution A; pour 2-3.5 mL of the dispersant into 6-10 mL of a 2.5 mol / L ammonium fluoride solution, and ultrasonically treat for 20-30 min to obtain solution B; ② Under stirring conditions, slowly add solution A to solution B. After the addition is complete, react for 40-60 minutes and then allow to stand for 2-3 hours. ③ Centrifuge at a speed of 3500-4000 r / min for 45-60 minutes, then wash with distilled water for 3-5 times, and finally dry in a drying oven at 55-65°C for 6-8 hours to obtain nano calcium fluoride.
Citation Information
Patent Citations
Wear-resistant zirconia ceramics
CN108558393B